PEMIKIRAN KALAM DALAM KONTEKS KEKINIAN - Ahmad, Kursani (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2013)
Islamic theology with theosentric paradigm was considered as something that must be shifted because the theology could not solve the contemporary problems that faced by Islam. During this time, classical theology considered stuck in the problems that are too soar and do not touch humanitarian problems such as poverty, corruption and oppression. Therefore, some Islamic thinkers such as Hasan Hanafi, Asghar Ali Engineer, and Nurcholis Madjid offered an alternative theology which is counted more grounded. Theology with this paradigm commonly referred to anthropocentric view.